Defender of the faithful : the life and thought of Rabbi Levi Yitsḥak of Berdychiv - Green, Arthur, 1941- (Tauber Institute for the Study of European Jewry series (Unnumbered), 2022)
"Defender of the Faithful is an intellectual and religious biography of Levi Yitshak of Berdychiv (1740-1809), one of the most fascinating and colorful Hasidic leaders of his time. Featuring examples of Levi Yitshak's extraordinary texts alongside insightful analysis, Arthur Green examines both Levi Yitshak's theology and broader philosophy"--